An Analysis of Integrated Occupational Health Effort Posts (Pos UKK) Policy in Fishermen’s Group in Lumajang Regency - Ayu Wulandari; Isa Ma’rufi; Hadi Prayitno (Aloha International Journal of Health Advancement (AIJHA), 2019)
The present study analyzes the suboptimal implementation of the Integrated Occupational Health Effort Post (Pos UKK) Policy in Fishermen’s Group in Lumajang Regency. The purpose of the study was to analyze the health policy in the form of Regent Regulation no. 18 of 2018 on Integrated Occupational Health Effort Post. This study applied qualitative approach with case study design. The data were collected through in-depth interview with the actor of the policy, triangulated with field observation and documentation. The present study employed Delphi method, it was aimed at formulating, prioritizing, and designing resolution strategy of policy problems. The result of the analysis found four variables affecting performance and impact of the decentralized policy. Study on these four variables was useful for understanding the suboptimal implementation of integrated pos UKK policy in fishermen’s group. Keywords: policy analysis; Occupational Health Effort (UKK) Post; Delphi method